(untitled) (Universal International Scientific Journal, 2026)
This thesis examines the psychological characteristics of personality development during adolescence. The study analyzes adolescents’ internal motivation, selfawareness, decision-making abilities, and social adaptation processes. The role of family, school, and peer groups in shaping adolescent development is highlighted. The results indicate that a supportive family atmosphere and engaged educational guidance play a key role in helping adolescents develop into resilient and socially skilled individuals.